Role of Dhaka Metropolitan Police (DMP) in present traffic management system of Dhaka City - Arif, Md. Shamsul (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.